2006
DOI: 10.1299/jsmeb.49.125
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Recovery in a Centrifugal Blower Casing

Abstract: The rate of circulating flow passing through the tongue division and the pressure recovery in the casing are investigated in a centrifugal blower, which has no diffuser and large tongue clearance. At the design point, the ratio of circulating flow rate to total flow rate at the scroll end is about 45 percent, and the pressure recovery in the scroll is about 45 percent. As the remaining 55 percent of the pressure recovery in the casing is recovered in the section between the scroll end and exit duct, this secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Many scholars have optimized the structural parameters of the volute [12][13][14][15]. Zhan et al [16] studied the influence of the relative position of impeller and volute by orthogonal test, and found that the efficiency could be increased by 1.26% after the position of impeller was adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have optimized the structural parameters of the volute [12][13][14][15]. Zhan et al [16] studied the influence of the relative position of impeller and volute by orthogonal test, and found that the efficiency could be increased by 1.26% after the position of impeller was adjusted.…”
Section: Introductionmentioning
confidence: 99%